TRPV4 Plays a Role in Matrix Stiffness-Induced Macrophage Polarization - Dutta, Bidisha; Goswami, Rishov; Rahaman, Shaik O. (Frontiers in Immunology, 2020)
Phenotypic polarization of macrophages is deemed essential in innate immunity and various pathophysiological conditions. We have now determined key aspects of the molecular mechanism by which mechanical cues regulate macrophage polarization. We show that Transient Receptor Potential Vanilloid 4 (TRPV4), a mechanosensitive ion channel, mediates substrate stiffness-induced macrophage polarization. Using atomic force microscopy, we showed that genetic ablation of TRPV4 function abrogated fibrosis-induced matrix stiffness generation in skin tissues. We have determined that stiffer skin tissue promotes the M1 macrophage subtype in a TRPV4-dependent manner; soft tissue does not. These findings were further validated by our in vitro results which showed that stiff matrix (50 kPa) alone increased expression of macrophage M1 markers in a TRPV4-dependent manner, and this response was further augmented by the addition of soluble factors; neither of which occurred with soft matrix (1 kPa). A direct requirement for TRPV4 in M1 macrophage polarization in response to increased stiffness was evident from results of gain-of-function assays, where reintroduction of TRPV4 significantly upregulated the expression of M1 markers in TRPV4 KO macrophages. Together, these data provide new insights regarding the role of TRPV4 in matrix stiffness-induced macrophage polarization that may be explored in tissue engineering and regenerative medicine and targeted therapeutics.